Death in the clouds - Christie, Agatha (Collins London, 2012)
Hercule Poirot is travelling from France to England by plane. During the journey one of his fellow passengers is murdered - but which of the 12 people on the plane is guilty of the crime? What motive could they have for murdering an elderly lady? And, most curiously of all, why did nobody see a thing?